Comparative performance of KiwiCross™, Holstein and Jersey dairy cattle on pasture herds in KwaZulu-Natal - Van Marle-Koster, Este (University of Pretoria, 2022)
Dissertation (MScAgric (Livestock Production))--University of Pretoria, 2022.